THE FORMULATION OF INDICATOR IN TEACHER’S SYLLABUS ON SPEAKING SKILL - Putu Ngurah Rusmawan (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2016)
KTSP (School Based Curriculum) is still widely applied in some school in Indonesia. Every school has given authority to make a syllabus. However, the teacher still gets difficulty to design syllabus. The teacher cannot identify the indicator from basic competence well. It meant that the teacher can not understand about the formulation of basic competence, so they can not identify indicator well. Finally, the can not developing the syllabus become lesson plan well. Teacher’s syllabus is a scenario when the teacher teaches their students in class. Teacher writes a syllabus for one semester, it is important for guidance of the teacher. In syllabus, teacher should interpret basic competence into systematic indicator. At least, syllabus consists of school identity, basic competence (KD), Sub KD, Sub-sub KD (it is written when basic competence consists more than one competence), indicator of competence, material, teaching and learning procedure, assessment, learning source, and media.This study related to the syllabus developed by the English teacher. The main data was a document made by the teacher. It would describe qualitatively. The researcher used the result of observation guidelines of ideal syllabus and table of operational KD and Indicator.Based on the result of the study, there are some points that can be known. (1) Most of the syllabus is not ideal. (2) Most of the syllabus is not used operational verb in KD and indicator. It means that most of the teachers are still difficult to identify KD and indicator. In conclusion, most of the teacher can not develop lesson plan well, because they can not identify indicator from basic competence well. If the teacher can not identify indicator from KD well, it can not make a systematic indicator. Systematic indicators determine about material, teaching and learning procedure, allocation of time, assessment, source and media. It means that an ideal syllabus, it can determine achievement of teaching learning in the class.